Effects of Boesenbergia rotunda juice on sperm qualities in male rats - Yotarlai S. (2014)
Boesenbergia rotunda (L.) Mansf. is one of Thai medicinal plants locally known for its male sexual enhancing effect. However, the study of other impacts of this plant on the male reproductive system is still very rare. To investigate the effects of B. rotunda on sperm qualities, the fresh juice of this plant was tested on both pre-mature and mature male rats by oral administration at the doses of 60, 120 and 600 mg/kg.bw for 30 days. The results showed that B. rotunda juice significantly progressively increased the motility of sperm at the doses of 60 and 120 mg/kg.bw and enhanced the number of normal sperm at all doses in the mature rats. Additionally, significant prominent stages VII to VIII of seminiferous epithelium was found in treated mature rats at all doses. There was no effect of B. rotunda on the pre-mature rats. These findings suggest that the B. rotunda juices could enhance fertility by improving the quality of sperm and its effect is age dependable. © 2011 Academic Journals.